KOPI, WARUNG KOPI, DAN POTENSI STUDI KEISLAMAN - Aflahal Misbah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
Coffee and coffee shop became the subject of study that was not much considered in Islamic studies, although both of its position is very significant in Muslim society. This study tries to see the potential area of Islamic discourses related to coffee and coffee shop. Based on an interdisciplinary approach, wherein the data derived from literature and ethnographic studies, the result revealed that there are set of matters which were missed by scholarly attention in the flow of changes and developments of Muslim society, both in the historical and contemporary space. There are a number of potential areas of the Islamic studies that can be developed through coffee and coffee shops, including the study of texts that include particular historical narratives and historical ideas related to these two material elements; Sufism, coffee, and coffee shop interrelations; the presence of Muslim women in public spaces, especially in the coffee shops; and harmony and diversity as a result of Muslim encounters with coffee and coffee shops, which can be seen for example through the framework of inter-religious relations.